The Development of the Home Recording Industry in the City of Padang Panjang - INDRA ARIFIN (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2020)
This research have a purpose to see how far the home recording industry has developed in the city of Padang Panjang. Generally, the home recording industry players in the city of Padang Panjang are dominated by students and graduates of the Indonesian Institute of the Arts, Padangpanjang. Therefore this research is focused on the city of Padang Panjang in order to see the correlation between the ISI Padang Panjang and the people of the city of Padang Panjang. The data analysis starts from the historical scope of the music recording industry on a large scale until it ends in a smaller scope, namely the city of Padang Panjang. This study uses a qualitative descriptive approach with several points to be examined, namely thery and development of the home recording industry, the number of home recording players in the city of Padang Panjang, how the work processes and stages, the number of service users, and the impact on the economy.